"Cloning, Gene Expression, and Protein Purification: Experimental Procedures and Process Ralionale" - Hardin (Charles); Edwards (Jennifer); Riell (Andrew); Presutti (David) & Others; Miller (William); Robertson (Dominique) (2008)
"Gene, Genome"
22.5
Keywords: "Gene, Genome"